Cross-cultural adaption of the Knee injury and Osteoarthritis Outcome Score (KOOS) into Punjabi for knee injury and osteoarthritis patients in Canada - Nitya Suryaprakash; Jackie L. Whittaker; Marie Westby; Richard Sawatzky; Stirling Bryan; Kusum Soni; Kamaljit Sidhu; Santosh Powar; Laurie J. Goldsmith (BMC Musculoskeletal Disorders, 2025)
Abstract Background The Knee injury and Osteoarthritis Outcome Score (KOOS) is a knee-specific patient-reported outcome that is used to assess knee-related symptoms, function and quality of life across a variety of knee conditions in patient populations. Currently there is no Punjabi version of the tool available. This study aims to cross-culturally adapt the KOOS tool from the source English language to the target Punjabi language for use in the Canadian health context. Methods We followed standard guidelines including: 1) creation of a concept definition document 2) forward translation 3) reconciliation 4) back translation 5) expert committee review 6) creation of pilot version for cognitive interviews 7) cognitive interviews 8) final review and proof reading. Results Thirty people identifying as South Asian with lived experiences of various knee conditions took part in cognitive interviews (70% women, mean age 61 years) to provide insights into equivalence in conceptual, semantic, and content between the source English language and the target Punjabi language KOOS. Cognitive interviews identified comprehension and interpretation, structural, conceptual, cultural, and other issues in the preliminary Punjabi KOOS. These issues were addressed considering the Punjabi audience and culture in Canada, and the purpose of the tool to arrive at a cross-culturally adapted Punjabi KOOS. Conclusion A cross-culturally Punjabi version of the KOOS is available to assess knee related outcomes of SA Punjabi patients in Canada. Future validation of the tool is required with SA Punjabi patients in Canada to ensure that the “target Punjabi instrument” has the same properties as the “original English KOOS instrument”.